Cataloguing and classifi cation in the era of artificial intelligence - Adeyinka Tella; Oluwole Akanmu Odunola; Wasiu. O. Lawal (Vjesnik Bibliotekara Hrvatske)
Goal: This study has examined cataloguing and classiﬁcation in the era of artiﬁcial intelligence, beneﬁts, and challenges from the perspective of cataloguing librarians in Oyo state, Nigeria.